Factors influencing health-related quality of life among knee and hip osteoarthritis patients in Kuala Nerus, Terengganu - Nur Aimi Asyrani binti Zamri
Osteoarthritis (OA) is the most prevalent chronic rheumatic disease and worldwide it is estimated to be the fourth source of pain and disability in most countries. According to the World Health Organisation (WHO), approximately 80% of people with OA have limitations in movement and 25% cannot perform their major daily activities, resulting in a significant decrease in their quality of life (QOL). Health-related quality of life (HRQOL) study on OA patients is lacking in Malaysia. Therefore, this study aimed to assess HRQOL and its factors among knee and hip OA patients. In this cross-sectional study, a total of 131 OA patients at rehabilitation phase were selected by using universal sampling from rehabilitation clinics or centres in Kuala ru, Terengganu. Socio-demographic, clinical, anthropometric measurements, HRQOL and lifestyle data were collected through questionnaires, while dietary intake was assessed by using a 24-hour dietary recall. Data were analysed by using SPSS package Version 22.0. Multiple linear regression was used to identify factors that influence the knee and hip OA patients. Knee and hip OA patients consisted of male (19.1 %) and female (80.9 %), with mean age of 62.0 ± 9.0 years (age range from 38 to 83 years). All patients were Malays, married (54.9%), received secondary education (48.8%), unemployed (79.4%), and with low income (90.8%). The majority of OA patients were having bilateral knee OA (49.6%), knee and hip OA (26.0%), right knee OA (12.2%) and left knee OA (12.2%). The mean of OA disease duration was 4.3 ± 4.7 years. The majority of OA patients had two non-communicable diseases (26.7%), in which hypertension (62.6%) and hyperlipidaemia (58.0%) were the most comorbidities recorded. The proportion of underweight, normal, overweight, and obese patients was 6.9%, 35.9%, 35.1 %, and 22.1%, respectively. Overall, the OA patients consumed 1,693 kcal/day, which comprised carbohydrates (227.1 g/day), protein (67.5 g/day) and fat (53.8g/day). Assessment of HRQOL showed that the highest mean score was by social functioning domain (41.25± 27.16) while the mental domain scored the least mean score (21.15±20.92). There was a significant difference between body fat and age groups (p=0.00 1), whereby OA patients of age less than 60 years were significantly higher in body fat. For the overall HRQOL, age, educational level, duration ofOA disease, hyperlipidaemia, types ofOA, number of comorbidities, types of treatment, vitamins (C, D, E, K), fat and exercise explained that variance (R2) in the final regression were 10.3%, 16.1 %,20.5%, 20.6% and 26.3% for pain, physical activity, mental, social support and social functioning, respectively. The present study found that the social functioning domain was the most affected HRQOL in knee and hip OA patients. Exercise showed that the main predictor factor associated with better HRQOL could serve as a basis in managing symptoms and preventing poor HRQOL that were tailored to this population.